Rekrutmen Politik Calon Kepala Daerah (Studi Tentang Seleksi Kandidat di Partai Keadilan Sejahtera Dalam Pemilukada Kota Tasikmalaya Tahun 2017) - Teguh Anggoro; Tina Cahya Mulyatin; Triono Triono (Jurnal Ilmu Politik dan Pemerintahan, 2020)
Recruitment of regional head candidates is part of the political process in the internal party in dealing with the General Election. Candidate selection is a "secret garden" for each party, besides the selection process is sometimes easily influenced by other forces outside political parties. Likewise, what happened in the selection process of candidates for regional head candidates in the DPD PKS at the Regional Election in Tasikmalaya City in 2017. This study was to answer the research question "What is the selection method in political recruitment of regional head candidates by the Prosperous Justice Party at the Regional Election in Tasikmalaya City 2017, What factors influence changes in the decision making of prospective regional heads by PKS ". This study aims to describe, analyze the selection of candidates, and explain the factors that influence the decision making of prospective regional head candidates from PKS. The results of this study explain the selection of PKS determined by party elites. At the local level the selection looks democratic while at the level of the DPW and DPP is strongly influenced by the party elite with a closed selection model. in general the candidate selection process at PKS shows non-democratic degrees.